2013
DOI: 10.2147/cia.s27931
|View full text |Cite
|
Sign up to set email alerts
|

Six-month leuprorelin acetate depot formulations in advanced prostate cancer: a clinical evaluation

Abstract: For nearly three decades, gonadotropin-releasing hormone (GnRH) agonists, particularly leuprorelin acetate (LA), have served as an important part of the treatment armamentarium for prostate cancer. The introduction of LA depot formulations provided a significant improvement in the acceptance of this therapy; however, their indicated treatment duration of 1 to 4 months was still not long enough to satisfy all medical needs. For this reason some manufacturers developed new injectable formulations that provide te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 40 publications
(42 reference statements)
1
3
0
Order By: Relevance
“…These two formulations guaranteed a similar release of leuprolide from the depot. The PK data obtained in this study for the 1-month depot are in agreement with the previously published results (Mazzei et al, 1990;Tunn et al, 2013;Zhou et al, 2021). Our results showed that changes in plasma leuprolide concentrations in the T and R depots were remarkably similar.…”
Section: Discussionsupporting
confidence: 93%
“…These two formulations guaranteed a similar release of leuprolide from the depot. The PK data obtained in this study for the 1-month depot are in agreement with the previously published results (Mazzei et al, 1990;Tunn et al, 2013;Zhou et al, 2021). Our results showed that changes in plasma leuprolide concentrations in the T and R depots were remarkably similar.…”
Section: Discussionsupporting
confidence: 93%
“…A few long-acting depot formulations have been developed using this approach. [1,2,[6][7][8][9][10][11][12][13][14] Although these drug carriers can extend the duration of drug action, their pharmacokinetic profiles are far from perfect. For example, for the PLGA microparticle approach, a characteristic tri-phased release, which is characterized by an initial burst release followed by a slow release phase and a final rapid release phase, is usually observed.…”
Section: Doi: 101002/mabi202000050mentioning
confidence: 99%
“…Hormone therapy and orchiectomy providing androgen deprivation have been established as the standard treatments for prostate cancer. The hormone therapy, monotherapy or combined androgen blockade therapy, includes luteinizing hormone-releasing hormone (LH-RH) agonists or an LH-RH antagonist that inhibits the production of testosterone following the suppression of gonadotropin release ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%